Exploring the health burden of cumulative and specific adverse childhood experiences in New Zealand: Results from a population-based study. (December 2021) - Hashemi, Ladan; Fanslow, Janet; Gulliver, Pauline; McIntosh, Tracey
Abstract: Background: Adverse childhood experiences (ACEs) can influence later health, but there are gaps in understanding how ACEs may interact with Positive Childhood Experiences (PCEs). Additionally, there are gaps in understanding how ACEs impact on positive markers of health. Objectives: To explore associations of ACEs with both negative and positive markers of physical and mental health in adulthood and to examine whether positive childhood experiences (PCEs) can mitigate the negative effects of ACEs on health. Participants and setting: 2887 participants (1464 female, 1423 male) from the 2019 New Zealand Family Violence Survey, a population-based study conducted in New Zealand between March 2017–March 2019. Methods: Multivariable logistic regressions were conducted to ascertain how both ACE score and ACE subtypes influenced the odds of experiencing adverse and positive mental and physical health after adjusting for socio-demographic predictors. A combined ACE-PCE variable was created and included in the multivariable logistic regression models to examine whether PCEs can mitigate the negative effects of ACEs. Results: Findings indicated that respondents with higher ACE scores had an increased likelihood of reporting each adverse outcome. Higher ACE scores had the strongest association with poor mental health followed by disability and chronic physical health conditions. Respondents with higher ACE scores had a decreased likelihood of reporting each positive health outcome. Exposure to ACEs was detrimental to health even in the presence of PCEs, with minimal effects observed from PCEs given the limited variance observed from its assessment. Conclusion: This study documents the deleterious impacts of ACEs on a wide range of health outcomes and demonstrates that these effects are persistent. Findings should provide the impetus for widespread prevention and intervention initiatives that seek to address ACEs. Further exploration of PCEs with a more complete assessment is needed to determine if they can mitigate the detrimental consequences of ACEs. Highlights: Higher ACE scores were associated with increased likelihood of reporting adverse outcomes. Higher ACE scores were associated with decreased likelihood of reporting positive outcomes. The enduring effects of ACEs on health were independent of sociodemographic characteristics, including economic factors.